(untitled) (Progressive Agriculture, 2019)
An experiment was conducted to evaluate eighteen Brassica genotypes for various morphological characters and estimate association for yield and yield contributing traits. The experimented was executed following Randomized complete block design (RCBD) with three replications in the experimental farm of the department of Genetics and Plant Breeding, Bangladesh Agricultural University Mymensingh-2202. The nine yield attributing characters are studied in the experiment. The genotypes differed significantly for all the traits viz., days to 1st flowering, days to maturity, plant height, number of branches/plant, number of pod/plant, length of pod, number of seeds/pod, 1000-seed weight (g) and seed yield/plant (g).Considering the two most important traits like early maturity and yield /plant, BD-7114 performed best among the studied genotypes. Correlation coefficients among the characters were studied to determine the association between yield and it attributing components. A significant positive correlation was found between yield and its attributing characters namely with number of seeds/pod and 1000-seed weight. Path analysis revealed both direct and indirect effects on seed yield and revealed that number of seeds/pod had the highest direct effect on seed yield. The findings of the research could be exploited in future breeding programs for improving Brassica genotypes. Progressive Agriculture 30 (1): 39-47, 2019